(untitled) (Global Journal of Human-Social Science, 2017)
Introduction-The raise of social networks in the last decades in various fields has called upon the need for their analysis. This phenomenon gave birth to Social Network Analysis (SNA) in the 1970s. Parallel to this quick development and the increasing need for such a methodology to analyze social networks, researchers developed a number of software for SNA. For these reasons, the authors of the present book (Borgatti, S. P., Everett, M. G. & Johnson, J. C.) made their practical guide about analyzing social networks available for researchers working on social media.